2021
DOI: 10.1021/acs.est.0c07880
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Microfauna Mechanisms for Sludge Reduction in Carrier-Enhanced Anaerobic Side-Stream Reactors Revealed by Metagenomic Sequencing Analysis

Abstract: Packing carriers into the anaerobic side-stream reactor (ASSR) can enhance sludge reduction and save footprint by investigating ASSR-coupled membrane bioreactors (AP-MBRs) under different hydraulic residence times of the ASSR (HRT SR ). Three AP-MBRs and an anoxic-aerobic MBR (AO-MBR) showed efficient chemical oxygen demand (>94.2%) and ammonium nitrogen removal (>99.3%). AP-MBRs have higher (p < 0.05) total nitrogen (61.4−67.7%) and total phosphorus (57.5−63.8%) removal than AO-MBRs (47.8 and 47.7%). AP-MBRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…COG 1506 in S. putrefaciens XY 07 was primarily associated with peptidases. Besides, COG 0308 (aminopeptidase) is one of the peptidases that can hydrolysis proteins . COG0814 (amino acid transport) and COG0697 (membrane) in S. putrefaciens XY 07 were involved in amino acid transport and metabolism; such ion transporters and a great variety of other highly specific transporters and permeases also play a vital role in marine bacteria .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COG 1506 in S. putrefaciens XY 07 was primarily associated with peptidases. Besides, COG 0308 (aminopeptidase) is one of the peptidases that can hydrolysis proteins . COG0814 (amino acid transport) and COG0697 (membrane) in S. putrefaciens XY 07 were involved in amino acid transport and metabolism; such ion transporters and a great variety of other highly specific transporters and permeases also play a vital role in marine bacteria .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, COG 0308 (aminopeptidase) is one of the peptidases that can hydrolysis proteins. 24 COG0814 (amino acid transport) and COG0697 (membrane) in S. putrefaciens XY 07 were involved in amino acid transport and metabolism; such ion transporters and a great variety of other highly specific transporters and permeases also play a vital role in marine bacteria. 25 A total of 226 genes were found in the S. putrefaciens XY 07 and annotated into energy production and conversion, of which the most abundant COGs were COG1053 (succinate dehydrogenase), COG1012 (dehydrogenase), COG0348 (4Fe-4S ferredoxin iron−sulfur binding domain protein), COG0243 (molybdopterin oxidoreductase), COG1301 (sodium dicarboxylate symporter), and COG0479 (succinate dehydrogenase).…”
Section: Genome Properties and Gene Function Analysismentioning
confidence: 99%
“…Small amounts of pedunculated or fixed ciliates were also identified (Figure 3). Among them, it was possible to identify the protozoan similar to Vorticella, which occurs in systems with good efficiency and well-oxygenated sludge (LEE et al, 2004;PAYANDEH;MEHRDADI;DADGAR, 2017;PONCE-ROBLES et al, 2018;JIANG et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Protozoa are known to play an essential role in filtering water and acting as potential bioindicators in wastewater treatment systems. However, many studies have reported that protozoa were observed in granules with bacteria and extracellular polymeric substances. The protozoa involved in these studies include ciliates, amoebae, and flagellates. Additionally, protozoa can attach to larger granules and be retained in systems with high settleability .…”
Section: Introductionmentioning
confidence: 99%